Adaptive design of long-focal-length freeform off-axis reflective space cameras with lightweight and integration of primary/tertiary mirror - Sun, Yiwei; Wei, Yangjie; Zhao, Ji (Frontiers in Physics, 2024)
With advancements in freeform surface design and manufacturing, applying freeform surfaces to space cameras is an effective method to further enhance imaging quality. However, existing design methods for freeform space cameras rarely consider imaging quality, system size, and manufacturing constraints simultaneously during design. This study proposes an adaptive design method for long-focal-length freeform off-axis reflective space cameras with lightweight and primary/three mirror integration, which balances system size and ease of manufacturing while ensuring good imaging quality. First, a method for adaptive configuration of the structural parameter search spaces is proposed, so that the search spaces for structural parameters are dynamically generated based on different design requirements of long-focal-length off-axis space cameras with various structures. Then, a multipleparameter objective function is constructed, and the structural parameters for the off-axis space camera are determined through a search process to balance imaging quality, lightweight requirements and manufacturing demands. Finally, the improved Wassermann-Wolf (W-W) method is employed to optimize the mirrors into freeform surfaces, further enhancing the imaging quality of the designed space camera. Experimental results demonstrate that the proposed method can adaptively generate reasonable structural parameter search spaces while maintaining high imaging quality, facilitating the acquisition of a lightweight and easily manufacturable freeform off-axis reflective space camera.